(3GdQSGdI GdcGTaI ddZeI aj GdGYJQGV Ydi GdGFeIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s ((3UdGM Hf eMeO Hf UdGM Hf Ydi Hf GdMSjf Hf YHO Gddg Hf jMji Hf MeRI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CXgQ HhLhO GdCFeI SdWGf GdESdGe CeG HYO aEf Gddg deG Yde ai bjGe GdCFeI ef GdeUGdM GdOjfjI hGdMce GdEdgjI hcGf ef dWa Gddg hJbOjQg s
(3BNQgG (B:s
(3hcGf EdbGDgG hLhGHgG eY TZd GdNGWQ HYeGQI gGJjf GdbdYJjf GdeHGQcJjf JeJ s
(3CLGH HgG GdeDda Ydi eSGFd hQOJ ef GdYQGb ef HOQ GdOjf eMeO Hf YHO Gddg Gdchai hGdPgdis
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3Gdabg GdESdGejs